On 'sticky' interior: Agglutinating as an interplay strategy for building adaptation - Verarisa Anastasia Ujung; Alya Amany (ARSNET, 2024)
This paper is an exploration into the idea of agglutinating as a building adaptation strategy. This paper examines agglutinating as a potential operation to address the interplay and affective relations between spatial elements, creating a 'sticky' interior which merges or combines these elements. The study in this paper addresses agglutination as the process of re-reading the site in evocative and productive ways, rediscovering the underlying architectural logic which generates new ideas. The study is based on a fourth-year interior architecture design studio project at the Universitas Indonesia, which focuses on various experiments in regard to the theme of adaptative reuse. The experimentation allows for a deep understanding of the agglutination operations and the resulting sticky interior, discovering the interplay between different layers of contexts, substances, contaminants, and temporalities. Through the agglutinating process, a series of affective qualities of the sticky interior are figured as a variety of adaptive operations: as zones of contact and encounter, as a channelling of bodily and spatial experiences, and as the interplay of preserved connection between objects, functions, as well as values. The glutinous capacity of spatial composition nurtures the project's dynamic through which playful and provocative design experimentations are performed.